Praktik Desentralisasi Asimetris di Indonesia - Rahmi Hayati; Muhammad Noor Ifansyah (Jurnal PubBis, 2019)
The biggest challenge in the practice of democracy is the process of sharing power, especially for the unitary state of Indonesia. The lack of clarity in the rule of law in the distribution of authority causes turbulence in resource-producing regions. The concept of asymmetric decentralization is one of the answers in the practice of democracy in Indonesia. Through a literature review approach, this paper tries to parse a few problems of asymmetric decentralization practices in Indonesia. It cannot be denied that this form of asymmetric decentralization is a logical consequence of democratic practices in Indonesia. Keywords: Asymmetric Decentralization